Evaluation of the implementation of Health Information System (Sistem Informasi Kesehatan Desa-SIKD) for Cadres in Penadaran Village, Grobogan Regency 2023 - Pramitasari, Ratih; Sifai, izzatul alifah; Febriyanto, Dwi Feri (Universitas Ahmad Dahlan, 2024)
Background: Health data reported by health cadres in villages is still done manually. Grobogan Regency needs to receive attention in health development in Central Java. Grobogan Regency's HDI in 2020 was 69.87, which was below the achievement of Central Java Province, namely 71.87 and National, 71.92. Method: This study aims to maximize the SIKD (Sistem Informasi Kesehatan Desa) which was a website-based data collection system developed by researchers to make it easier for village cadres to record health data. Results: This research was a descriptive analytic research with a qualitative approach with the aim of getting a picture or description of an actual situation. SIKD was tested for User Experience. This study took place in Penadaran Village, Gubug District, Grobogan Regency. It could be concluded that based on the results of the tests that have been carried out, the design that has been made has received a positive response and is worthy of being developed. SIKD is feasible to be developed. It was hoped that in the future, Conclusion: SIKD can be used as a data center that integrates all information systems and applications into a centralized database, so that it can be used by the wider community.